2022
DOI: 10.1371/journal.pone.0275170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, causes, and factors associated with obstructed labour among mothers who gave birth at public health facilities in Mojo Town, Central Ethiopia, 2019: A cross-sectional study

Abstract: Background Obstructed labour is a type of abnormal labour that is one of the causes of obstetric complications such as maternal and fetal mortality and morbidity. Early detection is the key to reducing complications. Objective This study aimed to assess the prevalence, causes, and factors associated with obstructed labor among mothers who gave birth at public health facilities in Mojo Town, Central Ethiopia. Methods An institution-based cross-sectional study was conducted from November 10 to December 30, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
1
1
Order By: Relevance
“…3 Duration of labor that persists ⩾24 hours were significantly associated with experiencing obstructed labor. This is in line with a study conducted in Adigrat Zonal Hospital, Tigray Region, Ethiopia reported that obstructed labor was highly prevalent among women who are in labor for a long time, 36 Metu Referal Hospital, Ilu Ababora Zone, Southwest Ethiopia, 18 Adama Hospital Medical College, 19 Mojo Town, Oromia, 34 Hawasa Town 37 and also abroad study reported that prolonged labor and obstructed labor were significantly associated. 7,38 Therefore, proper follow-up of danger signs of obstructed labor to women in labor and delivery and appropriate utilization of partograph to follow labor progress will help reduce the occurrence of obstructed labor which, in turn, decreases maternal mortality.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3 Duration of labor that persists ⩾24 hours were significantly associated with experiencing obstructed labor. This is in line with a study conducted in Adigrat Zonal Hospital, Tigray Region, Ethiopia reported that obstructed labor was highly prevalent among women who are in labor for a long time, 36 Metu Referal Hospital, Ilu Ababora Zone, Southwest Ethiopia, 18 Adama Hospital Medical College, 19 Mojo Town, Oromia, 34 Hawasa Town 37 and also abroad study reported that prolonged labor and obstructed labor were significantly associated. 7,38 Therefore, proper follow-up of danger signs of obstructed labor to women in labor and delivery and appropriate utilization of partograph to follow labor progress will help reduce the occurrence of obstructed labor which, in turn, decreases maternal mortality.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the prevalence of obstructed labor reported in this study is lower than the study conducted at Public Hospitals of Western Hararghe Zone, Oromia, Ethiopia in 2018 (34.3%), 33 Mojo Town, Oromia (22%), 34 and 20.5% prevalence of obstructed labor was reported in Nigeria. 35 The possible difference for this might be an improved healthcare system, proper care during pregnancy and delivery, and improved ANC follow-up in recent years than ever before.…”
Section: Discussioncontrasting
confidence: 83%
“…Fetal malpresentation and malposition were identified as other causes of prolonged and obstructed labor (Ayenew, 2021) leading to a greater risk of cesarean delivery (Senécal et al, 2005). Therefore, longer durations may be appropriate to reassure maternal and fetal status and continued descent of the fetal presenting part (Gill et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…One potential insult in the peripartum period is obstructed labour. Obstructed labour complicates 22% of pregnancies [ 12 ], and is involved in 50% of perinatal deaths [ 13 ] and 9% of maternal deaths [ 12 ] in Uganda. Unrelieved obstruction is associated with prolonged fetal asphyxia, which results in shunting of blood from the kidneys to maintain cerebral, cardiac, and adrenal perfusion [ 14 ].…”
Section: Introductionmentioning
confidence: 99%